Traditional decision-making for Indigenous child welfare - Lake, Chelsea; Lewis, Zach (Research Partnerships and Knowledge Mobilization, 2018)
By collaborating with First Nations and shifting child welfare policies to include traditional decision-making, governments may find solutions that meet the needs of Indigenous communities. Graduate Unreviewed